Transcutaneous auricular vagus nerve stimulation augments postprandial inhibition of ghrelin. Issue 8 (20th April 2022) - Kozorosky, Erica M.; Lee, Cristina H.; Lee, Jessica G.; Nunez Martinez, Valeria; Padayachee, Leandra E.; Stauss, Harald M.
Abstract: Vagus nerve stimulation (VNS) facilitates weight loss in animals and patients treated with VNS for depression or epilepsy. Likewise, chronic transcutaneous auricular VNS (taVNS) reduces weight gain and improves glucose tolerance in Zucker diabetic fatty rats. If these metabolic effects of taVNS observed in rats translate to humans is unknown. Therefore, the hypothesis of this study was that acute application of taVNS affects glucotropic and orexigenic hormones which could potentially facilitate weight loss and improve glucose tolerance if taVNS were applied chronically. In two single‐blinded randomized cross‐over protocols, blood glucose levels, plasma concentrations of insulin, C‐peptide, glucagon, leptin, and ghrelin, together with heart rate variability and baroreceptor‐heart rate reflex sensitivity were determined before and after taVNS (left ear, 10 Hz, 300 µs, 2.0–2.5 mA, 30 min) or sham‐taVNS (electrode attached to ear with the stimulator turned off). In a first protocol, subjects ( n  = 16) were fasted throughout the protocol and in a second protocol, subjects ( n  = 10) received a high‐calorie beverage (220 kCal) after the first blood sample, just before initiation of taVNS or sham‐taVNS. No significant effects of taVNS on heart rate variability and baroreceptor‐heart rate reflex sensitivity and only minor effects on glucotropic hormones were observed. However, in the second protocol taVNS significantly lowered postprandial plasma ghrelin levels (taVNS: −115.5 ± 28.3 pg/ml vs. sham‐taVNS: −51.2 ± 30.6 pg/ml, p  < 0.05). This finding provides a rationale for follow‐up studies testing the hypothesis that chronic application of taVNS may reduce food intake through inhibition of ghrelin and, therefore, may indirectly improve glucose tolerance through weight loss. Abstract : The results of this study show that noninvasive transcutaneous auricular vagus nerve stimulation (taVNS) augments the post‐prandial decline in plasma ghrelin levels. Since ghrelin is the "hunger hormone, " a greater post‐prandial decline in ghrelin is expected to increase satiety, prevent overeating during mealtime, and excessive snacking between meals. These potential effects of taVNS may help overweight or obese patients to lose weight.